Splenic Abscess in an Adolescent due to Salmonella enterica Conservatively Treated with Ultrasound-Guided Fine-Needle Aspiration - Anne Sofie Steinbring Jørgensen; Ivan Arsic; Niels Pedersen; Lena Hagelskjær Kristensen; Michael F. Nielsen; Thomas Balslev (Case Reports in Pediatrics)
Background. Splenic abscesses are rare and potentially fatal. Diagnosis is often delayed due to vague symptoms, and laboratory findings are varying and often nonspecific. Ultrasound and computed tomography have a high sensitivity in detecting splenic abscesses. Splenectomy was previously considered the gold standard for treatment, but in recent years, a shift has been seen towards a more conservative approach, i.e., ultrasound-guided aspiration or drainage in combination with adequate antibiotics in selected cases. Case Report. A previously healthy adolescent complained of left-sided chest pain, pain in the left clavicular region for three weeks, and recent fever. Ultrasound and computed tomography demonstrated an intrasplenic abscess. The patient was successfully treated with two percutaneous fine-needle punctures and adequate antibiotics for six weeks. Salmonella enterica serotype Poona was grown from the aspirate. At one-year follow-up, the patient remained healthy without signs of recurrence. Conclusion. The present case report demonstrates that ultrasound-guided aspiration and subsequent treatment with antibiotics may be an effective alternative to splenectomy in patients with a splenic abscess.